2014
DOI: 10.1016/j.saa.2013.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Second-order advantage obtained from standard addition first-order instrumental data and multivariate curve resolution-alternating least squares. Calculation of the feasible bands of results

Abstract: In order to achieve the second-order advantage, two-way data per sample are usually required, e.g., kinetic spectrophotometric data. In this study, instead of monitoring the time evolution of spectra (collecting kinetic-spectrophotometric data) replicate spectra are used to build a spectrophotometric data matrix which is rank deficient. Augmentation of these data with standard addition data [or standard sample(s)] will break the rank deficiency. making the quantification of the analyte of interest possible. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The baseline component was generated using the bilinear model given by Equation (2). The resulting data matrix with the baseline component, B, has the same dimensions as the pure chromatographic signal.…”
Section: Simulating the Baseline Component Of The Second-order Chromamentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline component was generated using the bilinear model given by Equation (2). The resulting data matrix with the baseline component, B, has the same dimensions as the pure chromatographic signal.…”
Section: Simulating the Baseline Component Of The Second-order Chromamentioning
confidence: 99%
“…Nonetheless, essential analytical information is often extracted from data that were recorded using advanced multichannel detectors. A unique advantage of the multichannel detectors, such as a diode-array detector, multiple fluorescence detector, or mass spectrometry is based on recording the existing differences in physicochemical properties of individual mixture components (absorption differences in the UV and/or Vis spectral range, ion velocity, and specific emission spectra), referred to as the second-order advantage in the literature [ 1 , 2 ]. Compared to the classic mono-channel counterparts, the subsequent portions of eluent are characterized by a multichannel detector to a larger extent in addition to the chromatographic separation that is carried out along the time domain.…”
Section: Introductionmentioning
confidence: 99%
“…Where C is the matrix of species' concentrations, S T is their corresponding pure spectra at the initial dye concentration, and E is the part of data that cannot be expressed by the model and contains an experimental error and/or noise. The ALS algorithm uses initial estimates of C 0 or S T 0 and optimizes them iteratively by least-square solution and the implementation of proper constraints such as nonnegativity, unimodality, equality and closure to find the best answers [32,33]. The optimized concentration profiles for each component can be applied to calculate the degradation efficiency values (Q) at each experiment using Eq.…”
Section: Mcr-als Analysismentioning
confidence: 99%
“…If the signals of the different analytes are not well resolved, calibration can be problematic. In the case of spectrophotometric measurements, second order information can be helpful to carry out calibration by standard addition, even using replicates of the samples to exploit the second-order advantage with first-order data [68]. In a recent work, our group has shown that the shape constraint characteristic of voltammetric measurements is a key factor to apply MCR-ALS to multivariate standard addition with no need of second order data.…”
Section: Determination and Speciation Of Heavy Metal Ions And Other P...mentioning
confidence: 99%